MICRO-FACTORS INFLUENCING SITE SELECTION FOR SMALL AND MEDIUM ENTERPRISES (SMES) IN SAUDI ARABIA: ALHASSA AREA USING ANALYTICAL HIERARCHY PROCESS (AHP) ANALYSIS - Al-Salamin, Hussain; Al-Baqshi, Jalal (European Scientific Journal, ESJ, 2015)
Site selection is a complex task for decision makers. However, this task becomes more complicated with small and medium enterprises. Location selection decision involves selected octal-factors which influence the decision. This paper proposed micro-factors that influence site selection decision with a quantitative tool (AHP analysis) to rank which factor is most significant and vice versa. Outcome of this paper considerably matches perspectives of experts and owners of small businesses in Al- Hassa area who gave an accurate estimation of factors prioritization due to their experience in the region as well as the businesses.